2016
DOI: 10.1038/nmicrobiol.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

MERS coronavirus induces apoptosis in kidney and lung by upregulating Smad7 and FGF2

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) causes sporadic zoonotic disease and healthcare-associated outbreaks in human. MERS is often complicated by acute respiratory distress syndrome (ARDS) and multi-organ failure(1,2). The high incidence of renal failure in MERS is a unique clinical feature not often found in other human coronavirus infections(3,4). Whether MERS-CoV infects the kidney and how it triggers renal failure are not understood(5,6). Here, we demonstrated renal infection and apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
169
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(172 citation statements)
references
References 33 publications
3
169
0
Order By: Relevance
“…Prior to December 2019, 6 CoVs were known to infect human, including 2 αCoV (HCoV-229E and HKU-NL63) and 4 βCoV (HCoV-OC43 [lineage A], HCoV-HKU1 [lineage A], SARS-CoV [lineage B] and MERS-CoV [lineage C]). The βCoV lineage A HCoV-OC43 and HCoV-HKU1 usually cause self-limiting upper respiratory infections in immunocompetent hosts and occasionally lower respiratory tract infections in immunocompromised hosts and elderly [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to December 2019, 6 CoVs were known to infect human, including 2 αCoV (HCoV-229E and HKU-NL63) and 4 βCoV (HCoV-OC43 [lineage A], HCoV-HKU1 [lineage A], SARS-CoV [lineage B] and MERS-CoV [lineage C]). The βCoV lineage A HCoV-OC43 and HCoV-HKU1 usually cause self-limiting upper respiratory infections in immunocompetent hosts and occasionally lower respiratory tract infections in immunocompromised hosts and elderly [4].…”
Section: Introductionmentioning
confidence: 99%
“…The βCoV lineage A HCoV-OC43 and HCoV-HKU1 usually cause self-limiting upper respiratory infections in immunocompetent hosts and occasionally lower respiratory tract infections in immunocompromised hosts and elderly [4]. In contrast, SARS-CoV (lineage B βCoV) and MERS-CoV (lineage C βCoV) may cause severe lower respiratory tract infection with acute respiratory distress syndrome and extrapulmonary manifestations, such as diarrhea, lymphopenia, deranged liver and renal function tests, and multiorgan dysfunction syndrome, among both immunocompetent and immunocompromised hosts with mortality rates of ∼10% and ∼35%, respectively [5,6]. On 31 December 2019, the World Health Organization (WHO) was informed of cases of pneumonia of unknown cause in Wuhan City, Hubei Province, China [7].…”
Section: Introductionmentioning
confidence: 99%
“…47 Further, ex vivo human kidney cultures were shown to support productive MERS-CoV infection. 48 However, it is not known whether infection of this organ contributes to worse outcomes compared with infections confined to the respiratory tract. Viral RNA, but not infectious MERS-CoV, was detected in the blood for at least 2 weeks after diagnosis.…”
Section: Pathogenesis and Pathologymentioning
confidence: 99%
“…33 Studies in kidney explants demonstrated infection of multiple cell types including renal tubular cells, vascular endothelial cells, and podocytes. 34 Experimental infection of small intestine explants with MERS-CoV demonstrated infection limited to the surface enterocytes and formation of syncytial cells. In keeping with these observations, infected patients have been found to shed virus in their urine and stool.…”
Section: Histopathologic Featuresmentioning
confidence: 99%